On the universal ultrametric space - Vestfrid, I. A (Ukrains’kyi Matematychnyi Zhurnal, 1994)
An ultrametric space in which any separable ultrametric space can be isometrically imbedded is constructed. We describe the method for isometric imbedding of any separable ultrametric space into l 1,l 2 andc 0 based on the application of this universal space.